Genetically predicted 486 blood metabolites in relation to risk of esophageal cancer: a Mendelian randomization study - Jia, Caiyan; Yi, Dan; Ma, Mingze; Xu, Qian; Ou, Yan; Kong, Fanming; Jia, Yingjie (Frontiers in Molecular Biosciences, 2024)
Background and Objective Enhancing therapy choices for varying stages of esophageal cancer and improving patient survival depend on timely and precise diagnosis. Blood metabolites may play a role in either causing or preventing esophageal cancer, but further research is needed to determine whether blood metabolites constitute a genetic risk factor for the disease. In order to tackle these problems, we evaluated the causal association between esophageal cancer and 486 blood metabolites that functioned as genetic proxies using a two-sample Mendelian randomization (MR) study. Methods We utilized two-sample MR analyses to evaluate the causal links between blood metabolites and esophageal cancer. For the exposure, we used a genome-wide association study (GWAS) of 486 metabolites, and a GWAS study on esophageal cancer from Sakaue et al. was used for preliminary analyses. Causal analyses employed randomized inverse variance weighted (IVW) as the main method, supplemented by MR-Egger and weighted median (WM) analyses. Sensitivity analyses included the MR-Egger intercept test, Cochran Q test, MR-PRESSO, and leave-one-out analysis. Additionally, independent esophageal cancer GWAS data were utilized for replication and meta-analysis. FDR correction was applied to discern features with causal relationships. For conclusive metabolite identification, we conducted Steiger tests, linkage disequilibrium score regression, and colocalization analyses. Moreover, we utilized the program MetaboAnalyst 5.0 to analyze metabolic pathways. Results This study found an important association between esophageal cancer and three metabolites: 1-linoleoylglycerophosphoethanolamine* [odds ratio (OR) = 3.21, 95% confidence interval (CI): 1.42–7.26, p < 0.01], pyroglutamine* (OR = 1.92, 95% CI: 1.17–3.17, p < 0.01), and laurate (12:0) (OR = 3.06, 95% CI: 1.38–6.78, p < 0.01). Conclusion This study establishes a causal link between three defined blood metabolites and esophageal cancer, offering fresh insights into its pathogenesis.